PERAN KEBIJAKAN LINGKUNGAN DALAM PEMBANGUNAN BERKELANJUTAN DI INDONESIA: STUDI KASUS SEKTOR KEHUTANAN - Aura Nafisah; Sesilia Grace Sitohang; Zulkarnaini (CV. ADIBA AISHA AMIRA, 2025)
This study aims to evaluate the role of Indonesia's forestry environmental policies (Moratorium, SVLK, Social Forestry) on achieving Sustainable Development, covering the ecological, economic, and social pillars. The method employed is qualitative policy analysis through desk research, analyzing secondary data from formal policy documents, government reports (KLHK deforestation trends), and academic/non-governmental studies. Research results show ambivalence. Ecologically, the Moratorium succeeded in stabilizing net deforestation, but mandatory SVLK serves as a non-tariff barrier for SMEs. In the social pillar, Social Forestry shows a significant economic impact (NEKON Rp1 trillion), yet target realization remains low (<50%) and the recognition process for Adat Forests is hindered by local regulations. The main challenge is governance, including the suboptimal capacity of Forest Management Units (KPH) and the risk of corruption, which erodes policy effectiveness at the ground level. Keywords: Environmental Policy, Forestry, Sustainable Development, Social Forestry, SVLK, FOLU Net Sink